Efecto del brebaje ayahuasca sobre la presión arterial, temperatura y actividad neurológica en ratas - Calderón Peña, Abhel Arthur (2017)
Abstract Ayahuasca is an herbal beverage, prepared ancestrally for medicinal and religious purposes. It is currently used in several drug addiction cure therapies and it has been researched the possibility that it has properties against some neurodegenerative diseases. In this study two plants were used as a part of the beverage known as "ayahuasca", Banisteriopsis caapi containing β-carbonyl alkaloids and Psychotria viridis containing N.N-dimethyltryptamine (DMT), which were mixed to prepare in a brew, which was administered to 40 experimental animals, in order to observe some physiological variables such as blood pressure, body temperature and neurological activity; which were measured each thirty minutes in a total time of ninety minutes. As a result, there was an increase in blood pressure between 30 to 60 minutes, increasing the systolic pressure of 114,0 to 127,9 mmHg and 114,2 to 125,1 mmHg respectively, with p <0,05; while there was no statistically significant variation for diastolic blood pressure (p> 0,05). The rectal temperature varied from 30 to 60 minutes, increasing from 36,18 to 38,03 °C and from 36,15 to 38,03 °C respectively, with p <0,05. Regarding the test of neurological activity for which the group was subjected, there were no significant changes in their behavior. In conclusion, the ayahuasca brew produces changes in the systolic blood pressure, the rectal temperature, but not in the neurological activity for the tests to which the rats were subjected.